Penciptaan Perempuan Pertama dalam Al-Qur'an (Studi Komparatif Penafsiran Wahbah Az-Zuhaili dan Buya Hamka) - Maesaroh, Dwi Siti (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study discusses the creation of the first woman in the Qur'an by comparing the interpretations between Wahbah az-Zuhaili who interpreted that women were created from a man's rib in the interpretations of al-Munir and Buya HAMKA who interpreted that women were created from the same elements as men Adam in the interpretation of al-Azhar. The research method used is a qualitative method with a comparative study. The results of this study indicate that az-Zuhaili's interpretation of the creation of the first woman is still conservative and the way of interpreting it is proven to be textual, even though he is a scholar in the contemporary century but unlike the majority of contemporary commentators who interpret the Qur'an contextually. Meanwhile HAMKA in its interpretation provides a more progressive explanation. HAMKA said that women were created from the same element as the Prophet Adam. Therefore, in interpreting the verses of the Qur'an, it will be better if you can understand what is meant by the verse being discussed, not just interpreting it dzhahir. As the results of HAMKA's interpretation which is more progressive because in understanding the authentic hadith which is used as the basis for interpretation by other commentators, it is understood in a majazi (figurative) way.